The implementation of the Trading Business License (SIUP) Permit Service at the Investment Agency, Integrated One-Stop Service Permit Service of Pangkalpinang City - Nugroho; Rachman, Bustami; Rulinawaty (International Journal of Science and Society, 2024)
This research investigates the implementation of the Trading Business License (SIUP) licensing service at the Investment Service, One Stop Integrated Licensing Service (PTSP) Pangkalpinang City. The method used in this research is qualitative, which was carried out through observation, interviews and documentation studies, and the Quantitative Method, which was collected through an evaluation survey of the level of satisfaction of entrepreneurs, was carried out through a direct survey of business permit applicants who had used the SIUP licensing service at PTSP Pangkalpinang City. This survey was conducted on 100 entrepreneurs in Pangkalpinang using a questionnaire based on satisfaction indicators, such as ease of licensing process, clarity of information provided, responsiveness of officers, and overall satisfaction with services. The research results show that although there are efforts to implement integrated licensing services, there are still challenges in integrating information systems, the quality of officer services, and the gap between entrepreneurs' expectations and reality. The implications of this research highlight the importance of improving technological infrastructure, training human resources, and improving licensing service policies and procedures to improve service quality and support economic growth in Pangkalpinang City.